Parameterization of the Farquhar-von Caemmerer-Berry C3 photosynthesis model for oil palm - S.S., Cheah; C.B.S., Teh (Institute of Experimental Botany of the Czech Academy of Sciences, 2020)
The Farquhar-von Caemmerer-Berry C3 photosynthesis (FvCB) model is used to model photosynthesis of oil palm. However, some model parameters and their temperature dependencies are not known for oil palm. Hence, the aim of this study was to determine the intercellular photocompensation point (Ci*), rate of leaf day respiration in the light (Rd), the chloroplastic photocompensation point (Γ*), mesophyll conductance (gm), maximum rates of Rubisco carboxylation (Vcmax) and electron transport (Jmax), triose phosphate utilization (TPU) and their temperature dependencies between 25 and 40°C in oil palm. Using leaf gas-exchange and chlorophyll fluorescence measurements, parameters such as Rd, Ci*, Γ*, gm, Vcmax, Jmax, and TPU were determined for oil palm. The parameters Ci*, Rd, Γ*, gm, and Vcmax responded to temperature exponentially without thermal deactivation. In contrast, Jmax and TPU responded to temperature exponentially up to 38°C before decreasing slightly at 40°C. Taken altogether, this study determined some key FvCB model parameters and their temperature dependencies for oil palm. This paves the way for more accurate modelling of photosynthetic carbon assimilation in oil palm particularly under future elevated temperatures and CO2 concentrations.